2021
DOI: 10.21115/jbes.v13.n2.p166-74
|View full text |Cite
|
Sign up to set email alerts
|

The use of micro-costing in an economic analysis of allogeneic HSCT in Brazil

Abstract: Objective: The objective of this study was to estimate treatment costs of Hematopoietic stem cell transplantation (HSCT) at a reference center in Brazil. Methods: The study population consisted of patients from the Unified Health System HSCT who underwent HSCT in southern Brazil between 2016 and 2019. Costs were measured using a micro-costing approach, based on Time-Driven Activity-based Costing (TDABC) adapted for economic studies in health and included the following steps: definition of the research question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This illustrates the significant heterogeneity in themes and applications in using TDABC. Despite having a high degree of heterogeneity (99.1%), this review demonstrated that the TDABC method can be applied to various conditions, allowing cost measurement through the best and most efficient method for cost measurement in healthcare [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This illustrates the significant heterogeneity in themes and applications in using TDABC. Despite having a high degree of heterogeneity (99.1%), this review demonstrated that the TDABC method can be applied to various conditions, allowing cost measurement through the best and most efficient method for cost measurement in healthcare [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TDABC method is considered the most precise method for measuring the costs of a specified clinical pathway due to its capability to measure the resources consumed by each patient based on two parameters: activity and time [ 8 , 9 ]. It accurately provides expenditures based on process maps to navigate the steps a patient must complete throughout their care cycle [ 10 ].…”
Section: Introductionmentioning
confidence: 99%